Conformational antigenic determinants generated by interactions between a bacterially expressed recombinant peptide of the hepatitis E virus structural protein - Zhang, Ji-Zhong; Ng, Mun H.; Xia, N. S.; Lau, S. H.; Che, X. Y.; Chau, T. N.; Lai, S. T.; Im, Stanley W. K. (Journal of medical virology, 2001)
A 23 kDa peptide locating to amino acid residues 394 to 604 of the major Hepatitis E Virus (HEV) structural protein was expressed in E. coli. This peptide was found to interact naturally with one another to form homodimers and it was recognized strongly and commonly in its dimeric form by HEV reactive human sera. The antigenic activity associated with the dimeric form was abrogated when the dimer was dissociated into monomer and the activity was reconstituted after the monomer was re‐associated into dimer again. The dimeric form of the peptide elicited a vigorous antibody response in experimental animals and the resulting antisera were found to cross‐react against HEV, effecting an efficient immune capture of the virus. These results attributed the antigenic activity associated with the dimeric form of the peptide to conformational antigenic determinants generated as a result of interaction between the peptide molecules. It is suggested that some of these antigenic determinants may be expressed by the HEV capsid and raised the possibility of this bacterially expressed peptide as an HEV vaccine candidate. J. Med. Virol. 64:125–132, 2001. © 2001 Wiley‐Liss, Inc.